Job Stress and Its Influence on University Staff’s Quality of Life: The Importance of Work-Life Balance and Coworker Support - Mukhlis, Hamid; Harlianty, Rully Afrita; Madila, Lina (Majalah Kesehatan Indonesia, 2024)
Quality of life plays a crucial role in enhancing employee productivity. This study aimed to assess the relationship between job stress and quality of life among university staff, identifying types of stress that positively or negatively impact well-being. A total of 88 university employees participated, with data collected using the New Job Stress Scale and WHOQOL, both adapted into Indonesian. Analyses included one-predictor regression, product moment correlation, independent t-test, and one-way ANOVA to evaluate job stress and quality of life. The results indicated that job stress predicts quality of life and is correlated with all its domains. Specific components of job stress, such as working time, work-related anxiety, role conflict, work-life balance, and coworker support, were significantly related to overall quality of life. No significant differences in job stress were observed based on gender, age, type of work, length of service, education level, or marital status. Similarly, quality of life did not vary by gender, age, type of work, education level, or marital status. However, significant differences in quality of life were found based on service length, with employees working more than five years reporting better quality of life than those with one to three years of service. The findings suggest universities should implement stress management programs and improve work-life balance policies to enhance staff well-being, particularly for long-serving employees.